Integration Potential of Russia in the Caspian Basin: Comparative Advantages and Risks - Nikolay V. GONTAR (Communications of International Proceedings, 2021)
The Caspian region today is an object of the integration policy of such world leaders as the USA, EU and China. Russia, being the closest and historically connected actor of processes in the basin, implements its integration strategies, the purpose of which is to strengthen Russia's positions both in the Caspian basin itself and in the vast part of Eurasia, including the Greater Caucasus, the Middle East and Central Asia. The article is devoted to the problem of positioning Russia in the Caspian basin in the context of the influence of states - Eurasian and global leaders. The aim of the study was to analyze the integration potential, mechanisms of interaction between key world powers and the basin countries, and to analyze the strengths and weaknesses of Russia in this process. On the basis of a comparative analysis of the forms of contacts between the countries of the basin and world powers, the key formats of integration activity in the region have been established. The current state of the key specializations of the basin is identified - production and transportation of hydrocarbons, transit function (including the North-South corridor). The comparative advantages and risks of Russia's implementation of integration with the basin countries are revealed. As part of the analysis, the economic potential of the Russian Caspian Sea region (structure and development formats) was structured. Prospective vectors of transformation of Russian policy in the Caspian Sea are proposed in order to enhance the potential of its integration influence.
Keywords: Economic integration; Eurasia; Caspian basin; Russia.